Direct observations of a Mt Everest snowstorm from the world's highest surface‐based radar observations. (16th October 2020) - Perry, L. Baker; Yuter, Sandra E.; Matthews, Tom; Wagnon, Patrick; Khadka, Arbindra; Aryal, Deepak; Shrestha, Dibas; Tait, Alex; Miller, Matthew A.; O'Neill, Alex; Rhodes, Spencer R.; Koch, Inka; et al.
Abstract : Ama Dablam (6812m) in the Khumbu (Everest) region as storm clouds build. (Photo credit: L.B. Perry/National Geographic.)